Synthesis of Xylitol-Polyester from Palm Fatty Acid Distillate(PFAD) - Suhardi .; Tranggono .; Amanda Hardiyani SN (Jurnal Teknologi dan Industri Pangan, 2003)
This study of xylitol-polyester synthesis was carried out using palm fatty acid distillate as the a source fatty acids. The objective of this study was to obtain the optimum condition with regard to reaction kinetis during synthesis. In the experiment, temperatures were varied at 110, 120, 130, 140 and 150oC; while during reactions samples were drawn at 0, 3, 6, 9 and 12 hours for determination of hydroxil value. Results showed that the optimum condition for synthesis was found at 145„b2.5oC for 3.5„b0.5 hours. It was noted, that the reaction was reversible, first order with the activation energy 4475.57 cal/mol for synthesis and 4499.21 cal/mol for hydrolisis.